1984
DOI: 10.1116/1.572749
|View full text |Cite
|
Sign up to set email alerts
|

Direct-current-magnetron deposition of molybdenum and tungsten with rf-substrate bias

Abstract: It has recently been shown that the stress of many refractory thin films deposited by dc-magnetron sputtering can be influenced by the sputtering pressure. Usually the transition from compressive to tensile stress is too sharp for pressure to be a reliable variable for stress control. This is particularly true in applications such as x-ray optics and lithography where extremely low stress is required owing to minimal substrate rigidity. In this paper, we show that there exists a broad region of the parameter s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0
1

Year Published

1985
1985
2015
2015

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(21 citation statements)
references
References 0 publications
1
19
0
1
Order By: Relevance
“…Impurities, especially oxygen, can enhance the formation and stability of b-W. [46][47][48][49][50] For example, b-W is mostly formed during hydrogen reduction of tungsten oxides. [51][52][53] In addition, a transition from the b to the a phase can be achieved by annealing above 700 C due to the removal of incorporated oxygen and enhancing the mobility of W atoms.…”
Section: Crystallinitymentioning
confidence: 99%
“…Impurities, especially oxygen, can enhance the formation and stability of b-W. [46][47][48][49][50] For example, b-W is mostly formed during hydrogen reduction of tungsten oxides. [51][52][53] In addition, a transition from the b to the a phase can be achieved by annealing above 700 C due to the removal of incorporated oxygen and enhancing the mobility of W atoms.…”
Section: Crystallinitymentioning
confidence: 99%
“…It is worthwhile to mention that stress becomes a critical point when the film thickness increases since typically larger stresses are observed for thicker films [17]. Indeed, Maier et al [18] reported that without specific substrate surface treatment, sufficient adhesion to the substrate was observed only for W coatings thinner than 1 m. Different approaches have been used to reduce stress in W thin films by using different methods: RFsubstrate biasing [19], plasma etching of the substrate [18], using a Cr sticking layer before the deposition of W [20]. However, most of these methods require double deposition procedure and plasma treatments which make somehow difficult the film deposition procedure.…”
Section: Introductionmentioning
confidence: 99%
“…Although the stable structure of tungsten is bcc ␣-W, [1][2][3][4][5] two other forms, nonequilibrium crystalline [6][7][8][9] ͑␤-W, with the A15 structure͒ and noncrystalline [10][11][12][13][14][15] structures, have long been recognized. From a technological point of view, disordered W materials are particularly attractive as thin films because noncrystalline films are able to tolerate more deleterious impurities, such as oxygen, carbon, nitrogen, hydrogen, etc., than crystalline W films.…”
Section: ͓S0003-6951͑99͒02341-4͔mentioning
confidence: 99%